2020
DOI: 10.1101/2020.08.14.240093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tissue-resident memory CD8 T-cell responses elicited by a single injection of a multi-target COVID-19 vaccine

Abstract: The COVID-19 pandemic is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) which enters the body principally through the nasal and larynx mucosa and progress to the lungs through the respiratory tract. SARS-CoV-2 replicates efficiently in respiratory epithelial cells motivating the development of alternative and rapidly scalable vaccine inducing mucosal protective and long-lasting immunity. We have previously developed an immunologically optimized multi-neoepitopes-based peptide vaccine pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 81 publications
(52 reference statements)
1
20
0
Order By: Relevance
“…What has not been demonstrated however, is whether any of these 1,500 predicted peptides are in fact processed and presented by SARS-CoV2+ cells and represent naturally-occurring epitopes recognized by T cells. A preliminary screen of predicted SARS-CoV2 epitopes considered "immunodominant" among widely cited reports appears to support this premise: previously we found that 7 of these 8 predicted peptides were unable to elicit a T cell response that would lead to recognition of SARS-CoV2+ targets suggesting that responses to these peptides may be artifactual, or at best cross-reactive (4,7,(15)(16)(17)(18)(19)(20)(21)(22) . To date, there has been no empiric validation of SARS-CoV2 epitopes for immunogenicity.…”
Section: Discussionmentioning
confidence: 75%
“…What has not been demonstrated however, is whether any of these 1,500 predicted peptides are in fact processed and presented by SARS-CoV2+ cells and represent naturally-occurring epitopes recognized by T cells. A preliminary screen of predicted SARS-CoV2 epitopes considered "immunodominant" among widely cited reports appears to support this premise: previously we found that 7 of these 8 predicted peptides were unable to elicit a T cell response that would lead to recognition of SARS-CoV2+ targets suggesting that responses to these peptides may be artifactual, or at best cross-reactive (4,7,(15)(16)(17)(18)(19)(20)(21)(22) . To date, there has been no empiric validation of SARS-CoV2 epitopes for immunogenicity.…”
Section: Discussionmentioning
confidence: 75%
“…While the role of the TH17 response in SARS-CoV-2 immunity remains to be determined, a robust TH17 response is important for promoting effective immunity to several respiratory viruses, including influenza virus, in which it is associated with enhanced viral clearance and survival 68,69 . In addition, TH17 lineage CD4 + T cells play a critical role in effective mucosal immunity and the development of TRM's in the lung, which increasing evidence supports, are critical elements of immunity to SARS-CoV-2 70 . Indeed, both NE and NE/IVT DI adjuvants induced S1-specific IgA in the bronchial alveolar lavage fluid (BAL) (Figure S2).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, NE and NE/IVT induced significant antigen-specific IgA in the bronchial alveolar lavage (BAL) of immunized animals (Figure S2). T H 17 CD4 + T cells are also critical for development of T RM ’s residing in the lung mucosa, which are critical elements of local immunity to SARS-CoV-2, functioning early before circulating effector and central memory cells are recruited 68, 69 . While IL-17A has been associated with lung pathology in certain situations, this is primarily observed in the context of high T H 2 cytokines, whereas pathological inflammatory effects of IL-17A are prevented by IL10 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Several groups are exploring the use of multi-epitope peptide vaccines against SARS-CoV-2; following bioinformatic and immune-informatic-based predictions of immunogenic epitopes [138][139][140][141], the studies are focusing upon T rather than B cell epitopes. OSE Immunotherapeutics have used a multiepitope peptide approach to induce T cell responses in mice [142]. Covaxx and the University of Nebraska Medical center have recently registered a Phase I clinical trial for a multi-epitope peptide vaccine (NCT04545749) as has the Vector Institute (NCT04527575) currently in clinical trial.…”
Section: Peptide Vaccinesmentioning
confidence: 99%